Promoting child-friendly school model through school committee as parents’ participation - Somariah Fitriani; Istaryatiningtias Istaryatiningtias (Institute of Advanced Engineering and Science, 2020)
The study intended to elaborate on the role of the school committee in addressing and promoting the implementation of the child-friendly school model to create a positive school climate and atmosphere. This qualitative approach research adopted a comparative case study since two primary schools become a unit of research analysis. Two primary schools, a public and private primary school in which both of them are located in Jakarta as a study site. The researchers obtained the data through observation, interviews, and document analysis. The research has revealed that the school committees, both in public and private schools, bring a vital contribution to help the schools in terms of supporting and controlling the implementation of the child-friendly school model with several different perspectives. The participation of the school committee is highly needed in monitoring the activity of the learning process toward the quality of school life and in bridging the communication between schools and students' parents, particularly in promoting the model of child-friendly school.